PENGARUH FUNGSI ACCOUNT REPRESENTATIVE TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Kasus pada KPP Pratama Malang Selatan) - Resika Puji Rahayu; Jimmy Andrianus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research has purpose to know influence of education, mentoring, and controlling of Account Representative to personal taxpayers compliance. This research has used quantitative approach. The variables of this research consists of education (X1), mentoring (X2), supervision (X3), and the compliance of personal taxpayers (Y). The sample used, namely 100 registered taxpayers in the Small Tax Office (STO) of South Malang. Sampling was done by distributing questionnaires directly to taxpayers who come to STO of South Malang. The sample was obtained from the calculation using the formula Slovin. Analysis of the data used in this research is multiple linear analysis. The results of the analysis of the data showed that partially education and mentoring function has no effect on a personal taxpayer compliance, but controlling functions have an influence on a personal taxpayer compliance in the sense that the higher level of supervision carried AR will be higher as well individual taxpayer compliance in STO South Malang. While simultaneously the function of education, mentoring, and controlling by the AR effect together against a personal taxpayer compliance in STO of South Malang. Based on the results of the test data is also showed that education, mentoring and controlling Account Representative has contributed 11.5% to the personal taxpayer compliance rate. Keywords: Education, Mentoring, Controlling, Account Representative, Personal Tax Payer Compliance